2021
DOI: 10.1177/21925682211006061
|View full text |Cite
|
Sign up to set email alerts
|

Annular Defects Impair the Mechanical Stability of the Intervertebral Disc

Abstract: Study Design: A biomechanical study. Objectives: The purpose of this study was to investigate the effects of cruciform and square incisions of annulus fibrosus (AF) on the mechanical stability of bovine intervertebral disc (IVD) in multiple degrees of freedom. Methods: Eight bovine caudal IVD motion segments (bone-disc-bone) were obtained from the local abattoir. Cruciform and square incisions were made at the right side of the specimen’s annulus using a surgical scalpel. Biomechanical testing of three-dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…AF sutures maintain IVD height and lumbar stability but do not provide high mechanical loading for long periods. Moreover, suture manipulation is difficult with larger defects ( Heuer et al, 2008 ; Rickers et al, 2018 ; Li et al, 2020 ; Ren et al, 2020 ; Chen et al, 2023 ). In the last decades, tissue-engineered biological repairs, such as hydrogels and scaffolds, has shown great advantages.…”
Section: Introductionmentioning
confidence: 99%
“…AF sutures maintain IVD height and lumbar stability but do not provide high mechanical loading for long periods. Moreover, suture manipulation is difficult with larger defects ( Heuer et al, 2008 ; Rickers et al, 2018 ; Li et al, 2020 ; Ren et al, 2020 ; Chen et al, 2023 ). In the last decades, tissue-engineered biological repairs, such as hydrogels and scaffolds, has shown great advantages.…”
Section: Introductionmentioning
confidence: 99%
“…At present, several animal models such as mice, 13 rats, 14 rabbits, 15 pigs, goats, 16 , 17 , 18 dogs, and nonhuman primates 19 , 20 have been extensively used for studying the reparative treatments to IVD‐related disorders; additionally, bovine coccygeal IVD has been frequently utilized as an organ culture model in vitro. 21 , 22 In these species, the rodents, rabbits, pigs, goats and dogs had the structure of vertebral growth plates that persisted through adulthood, and this structure was not seen in adult humans. 23 In some studies that used rodents as an animal model, the growth plate was mistakenly identified as the CEP; 24 it thus became meaningless to extrapolate the results found in the animals to the human CEP.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, a "limited" discectomy, even microendoscopic discectomy, which excises only fragments with minimal invasive exposure, was widely used to minimize the influence of segmental stability (3). However, the reoperation incidence persists at 13% to 25% after the limited discectomy procedure, mainly due to the symptomatic recurrent disc herniation presenting as the primary contributor (4)(5)(6). The annular defect because of the primary LDH or discectomy, especially for large and massive defect (≥ 6 mm), is considered the main reason for recurrent disc herniation (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%